The Ability to Write Imaginative Stories in Elementary School : (Analysis of Students of SD Negeri 3 Sukasari Kota Tasikmalaya) - Nurani, Riga Zahara; Sunendar, Dadang; Cahyani, Isah; Rakhmat, Cece (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
An Imaginative story texts are suggestive narrative essays that can help students use their reasoning skills and enhance their creativity. The problem of this research is how elementary school students can write imaginative story texts. This study aims to present an evaluation of the imaginative story texts from various aspects as an analysis of students’ abilities. This paper uses a quantitative approach with descriptive analysis methods. The data source was obtained from 24 texts collected from fifth-grade students. The research results show that students’ ability to write imaginative story texts is good in various aspects: (1) 100% in accordance with the theme/idea of the learning objective, (2) the plot of the story is good in 41.7% of the cases, sufficient in 50% of the cases, and poor in 8.3% of the cases, (3) the setting of the story is good in 41.7% of the cases and sufficient in 58.3% of the cases, (4) the portrayal of the characters is very good in 8.3% of the cases, good in 58.3% of the cases, and sufficient in 33.3% of the cases, (5) the insertion of the message is good in 33.3% of the cases, sufficient in 58.3% of the cases, and poor in 8.3% of the cases, (6) the language style is good in 66.7% of the cases and sufficient in 33.3% of the cases, (7) the use of the point of view is very good in 100% of the cases, (8) the organization and structure of the text is very good in 8.3% of the cases, good in 58.3% of the cases, and sufficient in 33.3% of the cases, (9) the spelling is very good in 8.3% of the cases, good in 41.7% of the cases, and sufficient in 50% of the cases, and (10) the neatness of the writing is good in 66.7% of the cases and sufficient in 33.3% of the cases. It can be concluded that out of the ten aspects evaluated, two aspects stand out, namely related to (1) the theme/idea being consistent with the learning objective, and (2) the use of the point of view.